Integrasi Kearifan Lokal dan Pengelolaan Lingkungan sebagai Strategi Pengembangan Ekonomi Tenun di Desa Wisata Bonjeruk - Imbuk Risnawati; Sarjan Sarjan (Pelantar Press, 2026)
This article discusses the integration of local wisdom and environmental management as a strategy for developing the weaving economy in Bonjeruk Tourism Village, Central Lombok. The traditional weaving industry, a cultural identity of the Bonjeruk community, currently faces the challenges of modernization, competition in the textile industry, and the risk of environmental degradation due to the use of synthetic materials. This research uses qualitative methods with a literature review approach, observation, and thematic analysis to explore local values, production practices, and the potential for developing a sustainability-based creative economy. The results of this study indicate that the integration of cultural values, natural dyeing techniques, and waste management can create an environmentally friendly creative economy model and increase the competitiveness of weaving. This article also formulates strategies for strengthening the ecoculture-based economy through cultural branding, artisan training, and multi-stakeholder collaboration